KEMAMPUAN ARTIKULASI BUNYI BAHASA ARAB PADA ANAK TUNARUNGU (Studi Kasus di SLB Negeri Sampang) - Iswah Adriana (Research Institute and Community Engagement of IAIN MADURA, 2017)
Human being using language through hearing by imitating language sound spoken by another people, but not all human beings born in a perfect condition. Some of them have weaknesses on their hearing which we called hearing impaired/ deaf. It is so because they lack and partly or totally loss their hearing ability because their hearing device does not work properly. The direct effect of hearing impaired/ deaf is the delaying verbal/ aural communication with other people, because we need a clear articulation or pronunciation to communicate with others so that the message can be well-delivered. As it has already known that there are some Arabic sounds that cannot be found in Indonesian, they are ح، خ، ز،ض،ص،ذ، ظ، ط،،ش therefore, as Moslems, the students with hearing impaired should not only be taught to pronounce clear indonesian sounds, but they also need to be trained to read al-Qur’an with the correct makharijul huruf. This study is trying to find out how well the students with hearing impaired pronounce Arabic sounds (both vowel and consonant) and also investigate the factors affecting the pronunciation. The result of the research is, (1) the majority of Arabic sound articulation pronounced by a student with hearing impaired (Lia) is not clear. Some of the consonants are ز،ر، س، ص, ع، ح ث، ذ، ظ, ق, ك، غ، خ, ف.. While in the vowel sound, it majority happenned in the short vowel sound I (kasrah), long vowel (mad), Harakat sukun and tasydid, while (2) some causing factors of the above problems are distortion, nasality (unclear sound production), and general and plural dyslalia.